PEMANFAATAN LIMBAH KOMODITAS PERKEBUNAN UNTUK PEMBUATAN ASAP CAIR / Utilization of Plantation Commodities Waste for Liquid Smoke - Sarwendah, Mamik; Feriadi, Feriadi; Wahyuni, Tri; Arisanti, Tiffani Nindya (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Liquid smoke is the result of condensation of smoke from the pyrolysis process of biomass containing elements of lignin and cellulose. The chemical and physical components of liquid smoke were determined by the raw materials used. The purpose of this study was to determine the characteristics of liquid smoke from different plantation wastes. The raw material used consists of coconut shells, palm shells, and sawdust. Coconut shells were obtained from coconut milk traders in the Pangkal Pinang market. Palm oil shells were taken from palm oil mill waste. Sawdust was a waste of wood craftsmen in Pangkalpinang. Liquid smoke was produced by pyrolysis using a simple tool consisting of a plate with the main components of a combustion tube, a smoke conduit pipe, and a condensing tube. This study used a randomized block design with five replications. The results showed the highest yield of liquid smoke was obtained from coconut shell compared to palm shell liquid and sawdust liquid smoke. Liquid smoke from coconut shel had lower pH and water content than that from oil palm shell and sawdust. The phenol content of coconut shell liquid smoke was 19.45 mg/ml, sawdust liquid smoke 8.24 mg/ml and oil palm shell liquid smoke 19.54 mg/ml. The acid content of coconut shell liquid smoke (7.44%) was higher than that of oil palm shell liquid smoke (5.70%) and sawdust (1.36%).Keywords: phenol, pyrolysis, coconut shell, oil palm shell AbstrakAsap cair merupakan hasil kondensasi asap dari proses pirolisis biomassa yang mengandung unsur lignin dan selulosa. Komponen kimia dan fisika asap cair ditentukan oleh bahan baku yang digunakan. Tujuan penelitian ini adalah untuk mengetahui karakteristik asap cair dari limbah komoditas perkebunan yang berbeda. Bahan baku yang digunakan terdiri dari tempurung kelapa, cangkang kelapa sawit dan serbuk gergaji. Tempurung kelapa diperoleh dari pedagang santan di pasar Pangkal Pinang. Cangkang kelapa sawit diambil dari limbah pabrik kelapa sawit. Serbuk gergaji merupakan limbah pengrajin kayu yang ada di Pangkalpinang. Pembuatan asap cair dilakukan dengan pirolisis menggunakan alat sederhana yang tediri dari plat dengan komponen utama tabung pembakaran, pipa penyalur asap, dan tabung kondensasi. Penelitian ini menggunakan rancangan acak kelompok dengan lima ulangan. Hasil penelitian menunjukkan rendemen asap cair dari tempurung kelapa paling tinggi dibandingkan dengan asap cair cangkang kelapa sawit dan serbuk gergaji. Asap cair tempurung kelapa mempunyai pH dan kadar air yang lebih rendah daripada asap cair cangkang kelapa sawit dan serbuk gergaji. Kandungan fenol asap cair tempurung kelapa 19,45 mg/ml, asap cair serbuk gergaji 8,24 mg/ml dan asap cair cangkang kelapa sawit 19,54 mg/ml. Kandungan asam asap cair tempurung kelapa (7,44%) lebih tinggi daripada asap cair cangkang kelapa sawit (5,70 %) dan serbuk gergaji (1,36 %).Kata kunci: fenol, pirolisis, tempurung kelapa, cangkang kelapa sawit